PECULIAR FEATURES OF ELECTROLYTIC-PLASMA HEATING DURING ELECTROCHEMICAL HEAT-TREATMENT OF STEEL - Yu. G. Alekseev; V. S. Niss; A. Yu. Korolyov; A. E. Parshuta (Наука и техника)
Thermo-physical peculiar features of  anode electrolytic-plasma heating applied for heat and chemical heat-treatment have been investigated in the paper. The paper presents  results of the investigations pertaining  to influence of the operating voltage on current density, temperature and heating rate, heating power and  changes in heat portion passing to the anode. Peculiar features of layer formation which are hardened  by electrolytic-plasma carburizing  have been presented in the paper.